Holcophloeus caldarai (Coleoptera: Curculionidae: Holcorhinini) a new weevil species from Morocco - Borovec, Roman; Košťál, Michael; Báborská, Zuzana (Zootaxa, 2018)
Holcophloeus caldarai sp. n. is described as a fifth species of the genus from central Morocco. The new species differs from all other species of the genus and, generally the entire tribe, by unique irregularly star-shaped appressed scales.